Laminated leadless piezoelectric ceramic, piezoelectric sensor and preparation method thereof
Through the stacked structure and components optimization, the problem of poor temperature stability of the barium zirconium titanate system is solved, and the stability of piezoelectric performance in a temperature fluctuating environment is improved.
Patent Information
- Application Number
- CN202510010205.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The temperature stability of the barium zirconium titanate system is poor, resulting in unstable piezoelectric performance under temperature fluctuations, affecting measurement accuracy and equipment reliability.
Lead-free piezoelectric ceramics with a laminated structure are used to adjust the component ratios of Ba(Zr0.2Ti0.8)O3 and (Ba0.7Ca0.3)TiO3 to form a solid solution, which improves the piezoelectric coefficient and temperature stability.
It effectively reduces piezoelectric performance fluctuations caused by temperature changes, improves the piezoelectric performance stability of ceramics over a wide temperature range, and enhances the reliability and measurement accuracy of the equipment.
Smart Images

Figure CN119707483A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of power electronic material preparation, and in particular to a laminated lead-free piezoelectric ceramic, a piezoelectric sensor and a preparation method thereof. Background Art
[0002] As an important functional material, piezoelectric materials are widely used in many fields such as industry and medicine. Lead zirconate titanate dominates the market due to its excellent piezoelectric properties and temperature stability. However, with the promulgation of the ban on lead in electronic devices in some regions, lead-free piezoelectric materials have become a research hotspot. Among them, the barium calcium zirconate titanate system has been favored by researchers because of its excellent electrical properties. Over the years, researchers have conducted systematic research on the source of the high piezoelectricity of the system and the preparation process. However, there are still some problems with the system, such as the lack of evidence of microscopic phase coexistence, insufficient research on equipment reliability, and poor temperature stability.
[0003] At present, the poor temperature stability of the barium calcium zirconate titanate system has become a major obstacle to its practical application. In some industrial environments that are sensitive to temperature changes, such as high-temperature manufacturing workshops or low-temperature refrigeration places, the piezoelectric performance of the system will change significantly due to temperature fluctuations, resulting in reduced measurement accuracy and unstable equipment operation. Summary of the invention
[0004] The present invention provides a laminated lead-free piezoelectric ceramic, a piezoelectric sensor and a preparation method thereof, which solves the technical problem of how to improve the stability of piezoelectric performance under a temperature fluctuation environment.
[0005] A first aspect of the present invention provides a laminated lead-free piezoelectric ceramic, comprising a plurality of lead-free piezoelectric ceramic layers;
[0006] The lead-free piezoelectric ceramic layers are laminated layer by layer to form a laminated lead-free piezoelectric ceramic;
[0007] The composition of each lead-free piezoelectric ceramic layer satisfies: (100-x) mol% Ba(Zr 0.2 Ti 0.8 )O3–xmol%(Ba 0.7 Ca 0.3 )TiO3, wherein x is a numerical value of molar percentage, 35≤x≤65.
[0008] Optionally, the number of layers of the lead-free piezoelectric ceramic layer is 2 to 5.
[0009] Optionally, the molar percentage values of the components of the multiple layers of the lead-free piezoelectric ceramic layers are distributed in a step-like manner and are different from each other.
[0010] Optionally, the components of the lead-free piezoelectric ceramic layers of the adjacent two layers are Ba(Zr 0.2 Ti 0.8 )O3 mole percentage and (Ba 0.7 Ca 0.3 )The numerical difference of the molar percentage of TiO3 is between 5 and 15 mol%.
[0011] Optionally, the piezoelectric coefficient of the stacked lead-free piezoelectric ceramic is 200-350 pc / N.
[0012] Optionally, the ceramic coercive field of the laminated lead-free piezoelectric ceramic is 1.8-2.8 kV / cm.
[0013] The second aspect of the present invention provides a method for preparing the laminated lead-free piezoelectric ceramic, comprising:
[0014] Barium source, calcium source, zirconium source and titanium source are used as raw materials. The raw materials are divided into the following components: (100-x)mol%Ba(Zr 0.2 Ti 0.8 )O3–xmol%(Ba 0.7 Ca 0.3 )TiO3 is prepared, wherein x is a value of molar percentage, 35≤x≤65;
[0015] Based on the above raw materials configured for each layer, powder preparation processing is performed respectively to obtain the second powder of each layer;
[0016] The second powder of each layer is post-processed to obtain a laminated lead-free piezoelectric ceramic.
[0017] Optionally, the raw materials configured on each layer are respectively subjected to powder preparation processing to obtain the second powder of each layer, including:
[0018] The above-mentioned raw materials prepared for each layer are mixed and subjected to a ball milling process to obtain the first slurry of each layer;
[0019] Sintering the first slurry of each layer to obtain the first powder of each layer;
[0020] The first powder of each layer is ball-milled for a second time to obtain the second slurry of each layer;
[0021] The second slurry of each layer is granulated to obtain the second powder of each layer.
[0022] A third aspect of the present invention provides a piezoelectric sensor, comprising a piezoelectric sensor element, an elastic diaphragm, a signal processing circuit and a housing, which are obtained by coating a layer of silver electrodes on the two end surfaces of the laminated lead-free piezoelectric ceramic obtained by the above-mentioned preparation method and then firing the resulting piezoelectric sensor element, an elastic diaphragm, a signal processing circuit and a housing;
[0023] The elastic diaphragm is arranged in the housing;
[0024] The piezoelectric sensing element is adhered to the elastic diaphragm;
[0025] The piezoelectric sensor element is connected to the signal processing circuit, and the signal processing circuit is used to perform charge conversion, amplification processing and filtering processing on the output signal.
[0026] A fourth aspect of the present invention provides a method for preparing the piezoelectric sensor, comprising:
[0027] A layer of silver electrode is coated on the two end surfaces of the stacked lead-free piezoelectric ceramic and the piezoelectric sensing element is obtained by integrated firing, wherein the integrated firing includes silver firing, polarization and packaging.
[0028] Paste the piezoelectric sensor element onto the elastic diaphragm;
[0029] connecting the electrodes of the piezoelectric sensing element to a signal processing circuit;
[0030] The assembled piezoelectric sensor element is placed in a housing for sealing and packaging to obtain a piezoelectric sensor.
[0031] It can be seen from the above technical solutions that the present invention has the following advantages:
[0032] The Ba(Zr) 0.2 Ti 0.8 )O3 and (Ba 0.7 Ca 0.3 )TiO3 are materials with high dielectric constants. By changing the ratio of Zr to Ti and the ratio of Ca to Ba, the phase boundary is adjusted. The two composites optimize the dielectric and piezoelectric properties of the ceramic. By adjusting the value x of the molar percentage, in order to 0.2 Ti 0.8 )O3 and (Ba 0.7 Ca 0.3 ) form a solid solution between lead-free piezoelectric ceramics and TiO3, thereby increasing the piezoelectric coefficient; the most important thing is that the two form a stable phase boundary, which improves the stability of the piezoelectric performance of lead-free piezoelectric ceramics in a wide temperature range. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0034] Figure 1The comparison diagram of the ceramic dielectric temperature spectrum obtained in Examples 1-3;
[0035] Figure 2 The figure is a comparison chart of the piezoelectric coefficients of the ceramics obtained in Examples 1-3 as the temperature changes;
[0036] Figure 3 The relationship between the polarization intensity and the electric field of the ceramics prepared in Examples 1-3 is a curve diagram;
[0037] Figure 4 The dielectric temperature spectrum result diagram of the single-layer system;
[0038] Figure 5 The piezoelectric coefficient of the single-layer system varies with temperature;
[0039] Figure 6 A flowchart of the steps of a method for preparing a laminated lead-free piezoelectric ceramic according to an embodiment of the present invention;
[0040] Figure 7 The present invention is a flowchart of a method for preparing a piezoelectric sensor according to an embodiment of the present invention. DETAILED DESCRIPTION
[0041] The embodiments of the present invention provide a laminated lead-free piezoelectric ceramic, a piezoelectric sensor and a preparation method thereof, which are used to solve the technical problem of how to improve the stability of piezoelectric performance under a temperature fluctuation environment.
[0042] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] In order to overcome the above-mentioned problem of poor temperature stability, the present invention proposes a laminated lead-free piezoelectric ceramic and a preparation method thereof. The laminated lead-free piezoelectric ceramic has 2 to 5 layers, and the components of each layer system meet the following requirements: (100-x)% molBa(Zr 0.2 Ti 0.8 )O3–xmol%(Ba 0.7 Ca 0.3 )TiO3, x is 35~60, Ba(Zr 0.2 Ti 0.8 )O3 and (Ba 0.7 Ca 0.3)TiO3 composite optimizes the phase change temperature and piezoelectric properties of the ceramic; the laminated structure further improves the temperature stability of the piezoelectric properties of the laminated lead-free piezoelectric ceramics in a wide temperature range.
[0044] The present invention provides a laminated lead-free piezoelectric ceramic, comprising multiple layers of lead-free piezoelectric ceramic layers;
[0045] Multiple layers of lead-free piezoelectric ceramics are laminated layer by layer to form a stacked lead-free piezoelectric ceramic;
[0046] The composition of each lead-free piezoelectric ceramic layer meets the following requirements: (100-x) mol% Ba(Zr 0.2 Ti 0.8 )O3–xmol%(Ba 0.7 Ca 0.3 )TiO3, wherein x is a numerical value of molar percentage, 35≤x≤65.
[0047] The number of lead-free piezoelectric ceramic layers is 2 to 5.
[0048] It should be noted that Ba(Zr 0.2 Ti 0.8 )O3 and (Ba 0.7 Ca 0.3 )TiO3 are all materials with high dielectric constants. By changing the ratio of Zr to Ti and the ratio of Ca to Ba, the phase boundary is adjusted. The two composites optimize the dielectric and piezoelectric properties of ceramics. By adjusting x, in Ba(Zr 0.2 Ti 0.8 )O3 and (Ba 0.7 Ca 0.3 )TiO3 forms a solid solution, thereby increasing the piezoelectric coefficient; the most important thing is that the two are combined to form a stable phase boundary, which improves the stability of the piezoelectric performance of the ceramic in a wide temperature range.
[0049] In the present invention, the laminated structure allows the ceramic phase boundaries to be distributed in a wider temperature range, effectively reducing the fluctuations in piezoelectric performance caused by temperature changes and improving the reliability of the ceramic in an environment of 25°C to 60°C; further, by adjusting the components of each layer, the ceramic exhibits excellent dielectric response characteristics within a specific temperature range, while improving the temperature stability of the piezoelectric performance of the ceramic; the laminated structure helps to relieve internal stress and improve the mechanical strength of the ceramic, making it more suitable for the mechanical requirements in practical applications.
[0050] It is worth mentioning that the laminated lead-free piezoelectric ceramic provided by the present invention takes the barium calcium zirconate titanate system as the research object, and improves the piezoelectric performance stability of the lead-free piezoelectric ceramic in a wide temperature range through the laminated structure.
[0051] The present invention provides a laminated lead-free piezoelectric ceramic, wherein the values of the molar percentages of the components of the multi-layer lead-free piezoelectric ceramic layers are distributed in a step-like manner and are different from each other.
[0052] It should be noted that in the present invention, the system components of each layer of the laminated lead-free piezoelectric ceramic are preferably stepped. If the system components of each layer of the laminated lead-free piezoelectric ceramic are consistent, the temperature stability is not very good. The stepped components make the chemical and physical properties between adjacent layers more compatible, thereby improving the bonding strength between layers and reducing interlayer defects.
[0053] It should be noted that the molar percentage values of the components of the multi-layer lead-free piezoelectric ceramic layers are different from each other, specifically referring to the different x values in the system components of each layer of the stacked lead-free piezoelectric ceramic.
[0054] The composition of the two adjacent lead-free piezoelectric ceramic layers is Ba(Zr 0.2 Ti 0.8 )O3 mole percentage and (Ba 0.7 Ca 0.3 )The numerical difference of the molar percentage of TiO3 is between 5 and 15 mol%.
[0055] It should be noted that the x difference in each layer system component is more appropriately between 5 and 15 mol%.
[0056] To make it easier to understand, here is an example of a multi-layer lead-free piezoelectric ceramic layer with a stepped distribution:
[0057] When the stacked lead-free piezoelectric ceramic includes 2 layers, the system components from top to bottom are:
[0058] 65mol%Ba(Zr 0.2 Ti 0.8 )O3-35mol%(Ba 0.7 Ca 0.3 )TiO3;
[0059] 50mol%Ba(Zr 0.2 Ti 0.8 )O3-50mol%(Ba 0.7 Ca 0.3 )TiO3.
[0060] When the stacked lead-free piezoelectric ceramic includes 3 layers, its system components from top to bottom are:
[0061] 65mol%Ba(Zr 0.2 Ti 0.8 )O3-35mol%(Ba 0.7 Ca 0.3 )TiO3;
[0062] 50mol%Ba(Zr 0.2 Ti 0.8 )O3-50mol%(Ba 0.7 Ca 0.3 )TiO3;
[0063] 40mol%Ba(Zr 0.2 Ti 0.8 )O3-60mol%(Ba 0.7 Ca 0.3 )TiO3.
[0064] When the stacked lead-free piezoelectric ceramic includes 5 layers, its system components from top to bottom are:
[0065] 65mol%Ba(Zr 0.2 Ti 0.8 )O3-35mol%(Ba 0.7 Ca 0.3 )TiO3;
[0066] 60mol%Ba(Zr 0.2 Ti 0.8 )O3-40mol%(Ba 0.7 Ca 0.3 )TiO3;
[0067] 55mol%Ba(Zr 0.2 Ti 0.8 )O3-45mol%(Ba 0.7 Ca 0.3 )TiO3;
[0068] 50mol%Ba(Zr 0.2 Ti 0.8 )O3-50mol%(Ba 0.7 Ca 0.3 )TiO3;
[0069] 45mol%Ba(Zr 0.2 Ti 0.8 )O3-55mol%(Ba 0.7 Ca 0.3 )TiO3.
[0070] It is worth mentioning that the laminated lead-free piezoelectric ceramics provided by the present invention achieve non-attenuation of the dielectric constant under the laminated structure by adjusting the proportion of the components of each layer. At the same time, the laminated lead-free piezoelectric ceramics exhibit excellent piezoelectric response characteristics within a specific temperature range, and can be used for the preparation of piezoelectric sensors under variable temperature scenarios.
[0071] The present invention provides a laminated lead-free piezoelectric ceramic, the piezoelectric coefficient of the laminated lead-free piezoelectric ceramic is 200-350pc / N.
[0072] The coercive field of the lead-free multilayer piezoelectric ceramics is 1.8~2.8 kV / cm.
[0073] Please note that Figure 1 , no obvious dielectric peak is observed in the temperature range of 25~80℃ for the laminated lead-free piezoelectric ceramics, so the dielectric response of the laminated lead-free piezoelectric ceramics has good temperature stability; the piezoelectric coefficient of the laminated lead-free piezoelectric ceramics at room temperature is 200~350pc / N, and the coercive field is 1.8~2.8 kV / cm. Combined with the above, it can be seen that preferably, the operating temperature of the laminated lead-free piezoelectric ceramics is 25~80℃, and more preferably, the operating temperature of the laminated lead-free piezoelectric ceramics is 25~60℃.
[0074] See also Figure 6 The present invention provides a method for preparing a lead-free laminated piezoelectric ceramic, comprising:
[0075] Step 101: Using barium source, calcium source, zirconium source and titanium source as raw materials, the raw materials are divided into the following components: (100-x) mol% Ba(Zr 0.2 Ti 0.8 )O3–xmol%(Ba 0.7 Ca 0.3 )TiO3 is prepared, wherein x is a value of molar percentage, 35≤x≤65.
[0076] In the embodiment of the present invention, the usage ratio of the barium source, the calcium source, the zirconium source and the titanium source satisfies (100-x)% molBa(Zr 0.2 Ti 0.8 )O3–xmol%(Ba 0.7 Ca 0.3 )TiO3, x is 35 to 60. Since the laminated lead-free piezoelectric ceramic is a laminated structure, the components of each layer system may be the same or different, preferably different, and the components of each layer system are more preferably stepped. Preferably, each layer system is respectively subjected to the above steps 101 to 102 according to its respective dosage, and then the laminated lead-free piezoelectric ceramic is prepared according to step 103.
[0077] Furthermore, when the stacked lead-free piezoelectric ceramic includes two layers, that is, two system components, the amount ratio of BaCO3, CaCO3, TiO2, and ZrO2 in one system satisfies 65mol%Ba(Zr 0.2 Ti 0.8 )O3-35mol%(Ba 0.7 Ca 0.3)TiO3, the other system has a ratio of BaCO3, CaCO3, TiO2, and ZrO2 that satisfies 50mol%Ba(Zr 0.2 Ti 0.8 )O3-50mol%(Ba 0.7 Ca 0.3 )TiO3.
[0078] When the stacked lead-free piezoelectric ceramic includes three layers, namely three system components, the amount ratio of BaCO3, CaCO3, TiO2 and ZrO2 in one system satisfies 65mol%Ba(Zr 0.2 Ti 0.8 )O3-35mol%(Ba 0.7 Ca 0.3 )TiO3; in another system, the ratio of BaCO3, CaCO3, TiO2, and ZrO2 satisfies 50mol%Ba(Zr 0.2 Ti 0.8 )O3-50mol%(Ba 0.7 Ca 0.3 )TiO3; there is also a system in which the amount ratio of BaCO3, CaCO3, TiO2, and ZrO2 satisfies 40mol%Ba(Zr 0.2 Ti 0.8 )O3-60mol%(Ba 0.7 Ca 0.3 )TiO3.
[0079] When the stacked lead-free piezoelectric ceramic includes 5 layers, that is, 5 system components, the dosage ratios of BaCO3, CaCO3, TiO2, and ZrO2 in the 5 systems are:
[0080] 65mol%Ba(Zr 0.2 Ti 0.8 )O3-35mol%(Ba 0.7 Ca 0.3 )TiO3;
[0081] 60mol%Ba(Zr 0.2 Ti 0.8 )O3-40mol%(Ba 0.7 Ca 0.3 )TiO3;
[0082] 55mol%Ba(Zr 0.2 Ti 0.8 )O3-45mol%(Ba 0.7 Ca 0.3 )TiO3;
[0083] 50mol%Ba(Zr 0.2Ti 0.8 )O3-50mol%(Ba 0.7 Ca 0.3 )TiO3;
[0084] 45mol%Ba(Zr 0.2 Ti 0.8 )O3-55mol%(Ba 0.7 Ca 0.3 )TiO3.
[0085] Step 102: Powder preparation is performed based on the above raw materials configured for each layer to obtain second powder for each layer.
[0086] Further, step 102 may include the following sub-steps:
[0087] S11, mixing the above-mentioned raw materials prepared for each layer, and performing a ball milling process to obtain the first slurry of each layer.
[0088] In the embodiment of the present invention, further, the barium source is preferably barium carbonate and / or barium titanate, more preferably barium carbonate.
[0089] Among them, the barium source provides barium ions. Barium carbonate is more stable, and the barium oxide obtained by decomposition during sintering reacts with other raw materials to form a perovskite structure; the decomposed carbon dioxide acts as a sintering aid to promote densification.
[0090] Furthermore, the calcium source is preferably calcium carbonate and / or calcium zirconate, more preferably calcium carbonate.
[0091] Among them, the introduction of calcium helps to change the phase transition temperature, and the calcium ions and barium ions form a solid solution, which is beneficial to optimize the piezoelectric properties.
[0092] Furthermore, the zirconium source is preferably barium zirconate and / or zirconium dioxide, preferably zirconium dioxide.
[0093] Among them, zirconium ions in the zirconium source partially replace titanium ions, stabilize the lattice structure of barium titanate, and zirconium ions help to inhibit grain growth; and help to improve the piezoelectric resistance of ceramics, making them more stable under the action of electric fields. Zirconium dioxide has lower costs and better chemical stability at high temperatures, and it reacts with barium oxide to form a solid solution.
[0094] Furthermore, the titanium source is preferably titanium dioxide and / or barium titanate, preferably titanium dioxide.
[0095] Among them, titanium ions in the titanium source help to form and regulate electric domains, which is the key to the piezoelectric effect. High-purity titanium dioxide is conducive to the preparation of high-performance ceramics.
[0096] Furthermore, the barium source, calcium source, zirconium source and titanium source interact with each other, and the properties of the piezoelectric ceramics, such as the piezoelectric constant and the dielectric constant, are optimized by adjusting the ratio of the doping elements.
[0097] Furthermore, the ball milling medium used in the first ball milling is an alcohol solvent, preferably anhydrous ethanol which is non-toxic and safe to operate. The ball milling medium protects the raw materials during the first ball milling process, and ethanol has a low boiling point and is easily volatile, which is convenient for removal in the subsequent sintering process, and has low tension, which will not cause the first slurry to agglomerate.
[0098] Furthermore, the weight ratio of the mixture of the barium source, the calcium source, the zirconium source and the titanium source to the ball milling medium is 1:(1-3), preferably 1:(1-2), and more preferably 1:1.4.
[0099] Among them, if the ball milling medium is too little, it cannot fully protect the mixture, and if the ball milling medium is too much, the efficiency of the primary ball milling will be reduced.
[0100] Furthermore, the primary ball milling speed is 100-500 r / min, preferably 200-400 r / min, for example 300 r / min.
[0101] Among them, as the speed of the first ball milling increases, the powder particles become finer and the distribution becomes more uniform; however, too fast a speed of the first ball milling causes the first slurry to aggregate.
[0102] Furthermore, the ball milling time is 1 to 10 hours, preferably 3 to 5 hours, and more preferably 4 hours.
[0103] Among them, as the ball milling time increases, the first slurry is dispersed more and more evenly, but if the ball milling time is too long, the refining effect is not obvious, but the activity of the first slurry increases continuously during the first ball milling process, and the work hardening is serious.
[0104] S12, sintering the first slurry of each layer to obtain the first powder of each layer.
[0105] In the embodiment of the present invention, before sintering, the first slurry is dried and sieved to facilitate uniform heating during the sintering process.
[0106] Furthermore, the drying temperature is 60-80° C., and the drying time is 12-16 hours; for example, the drying temperature is 80° C., and the drying time is 12 hours; and the sieving is performed using 60-mesh and 100-mesh sieves in turn.
[0107] Furthermore, the sintering temperature is 1200-1400° C., preferably 1300-1400° C., for example 1350° C.; the sintering time is 3-6 hours, preferably 3-5 hours, for example 4 hours.
[0108] Among them, if the sintering temperature is too low, the chemical reaction between the substances cannot be fully carried out, and if the sintering time is too long, grain growth may occur.
[0109] S13, ball-milling the first powder of each layer for a second time to obtain the second slurry of each layer.
[0110] In the embodiment of the present invention, in order to refine the particle size of the first powder, the first powder is preferably sieved using 60-mesh and 100-mesh sieves in sequence.
[0111] Furthermore, the secondary ball milling helps to pulverize the first powder, which is convenient for subsequent granulation.
[0112] Furthermore, the secondary ball milling medium is an alcohol solvent, preferably anhydrous ethanol which is non-toxic and safe to operate.
[0113] Furthermore, the weight ratio of the first powder to the secondary ball milling medium is 1:(1-3), preferably 1:(1-2), and more preferably 1:1.4.
[0114] Furthermore, the secondary ball milling speed is 100-500 r / min, preferably 200-400 r / min, for example 300 r / min; the secondary ball milling time is 5-12 h, preferably 6-10 h, more preferably 8 h.
[0115] Furthermore, if the alcohol solvent used in the secondary ball milling is not removed, agglomeration will occur in the subsequent granulation process. Drying treatment can effectively reduce agglomeration and improve dispersibility.
[0116] Furthermore, the drying temperature and time only need to be able to remove the alcohol solvent. Generally, the drying temperature is 60-80°C and the time is 12-16 hours; for example, the drying temperature is 80°C and the time is 12 hours.
[0117] S14, granulating the second slurry of each layer to obtain the second powder of each layer.
[0118] In the embodiment of the present invention, the granulating agent selected during granulation is a water-soluble polymer, preferably polyvinyl alcohol glue.
[0119] Among them, water-soluble polymers have good adhesion, especially polyvinyl alcohol glue, which helps the molding and quality control of the final product, and is biodegradable and environmentally friendly.
[0120] Furthermore, the amount of the granulating agent added is 6-10 wt % of the mass of the second slurry, for example 8 wt %, which provides sufficient bonding force and maintains structural stability.
[0121] Furthermore, granulation is performed to obtain a second powder having a particle size between 60 and 100 meshes.
[0122] Step 103: Post-process the second powder of each layer to obtain a laminated lead-free piezoelectric ceramic.
[0123] In the embodiment of the present invention, the second powder of each layer is post-processed to obtain a laminated lead-free piezoelectric ceramic.
[0124] Furthermore, the post-processing includes: pressing into a blank, heat treatment, silver coating and silver burning.
[0125] Furthermore, the second powder is pressed into a billet, and the pressed billet is more easily densified during heat treatment because the pressing has provided a preliminary shape and structure, and heat treatment only requires further elimination of pores and promotion of grain growth.
[0126] Furthermore, during pressing, the system components are preferably stepped, and the systems are stacked in layers. Each stacked layer is pre-pressed once with a pressure of 0.5-1 MPa. After the stacking is completed, a pressure of 18-25 MPa, such as 20 MPa, is used to press for 2-5 min, such as 3 min, to obtain a blank.
[0127] Further, the heat treatment includes:
[0128] The first stage: heating from room temperature to 400~600℃ at a heating rate of 80~120℃ / h, and keeping warm for 0.5~2h;
[0129] The second stage: the temperature is raised from the first stage holding temperature to 1400~1600℃ at a heating rate of 80~120℃ / h, kept at this temperature for 2~6h, and then cooled naturally.
[0130] Among them, the first stage is mainly used for debinding, that is, removing the granulating agent without damaging the green body. 0.5~2h is enough for the granulating agent to volatilize without causing changes in the green body structure. In the above first and second stages, the lower heating rate and higher sintering temperature are conducive to the densification of the ceramic, so that the grains grow and the pores are reduced; the appropriate holding time is conducive to the diffusion of the material and the growth of the grains, but too long a time will lead to excessively large grains and secondary crystallization.
[0131] In a further preferred embodiment, the heat treatment comprises:
[0132] The first stage: heating from room temperature to 450~550℃ at a heating rate of 90~110℃ / h, and keeping warm for 1~1.5h;
[0133] The second stage: the temperature is raised from the first stage holding temperature to 1450~1550℃ at a heating rate of 90~110℃ / h, kept at this temperature for 3~5h, and then cooled naturally.
[0134] In a further preferred embodiment, the heat treatment comprises:
[0135] The first stage: heating from room temperature to 500℃ at a heating rate of 100℃ / h, and keeping the temperature for 1h;
[0136] The second stage: the temperature was raised from the first stage holding temperature to 1500°C at a heating rate of 100°C / h, kept at that temperature for 4h, and then cooled naturally.
[0137] Furthermore, after heat treatment, a laminated ceramic substrate is obtained, and then the upper and lower surfaces thereof are polished successively with sandpaper such as 600 mesh and 1000 mesh to remove the oxide layer or impurities formed on the surface during heat treatment and to improve the surface flatness.
[0138] Furthermore, a conductive layer is formed on the surface of the multilayer ceramic substrate by coating with silver to serve as a signal transmission path. Silver paste is coated on the upper and lower surfaces of the multilayer ceramic substrate.
[0139] Furthermore, the bonding strength between the silver layer and the laminated ceramic substrate is enhanced by silver sintering. Silver sintering includes: heating from room temperature to 600-900°C at a heating rate of 130-170°C / h, keeping the temperature for 20-60 minutes, and then cooling naturally; preferably, heating from room temperature to 700-850°C at a heating rate of 140-160°C / h, keeping the temperature for 30-50 minutes, and then cooling naturally; more preferably, heating from room temperature to 800°C at a heating rate of 150°C / h, keeping the temperature for 40 minutes, and then cooling naturally.
[0140] Among them, for the laminated ceramic substrate coated with silver paste, a slower heating rate helps the solvent in the silver paste to evaporate gradually, avoiding bubbles or cracks caused by rapid volatilization of the solvent due to rapid heating; the temperature of 600~900℃ can melt the silver particles and form a continuous conductive network; the holding time is long enough to ensure that the silver particles in the silver paste are fully melted and combined with the surface of the laminated ceramic substrate to form a uniform and dense conductive layer, and 20~60min is more appropriate.
[0141] The present invention is further described below through specific examples, but these examples are merely exemplary and do not constitute any limitation to the scope of protection of the present invention.
[0142] Example 1
[0143] In this embodiment, the ceramic is divided into two layers, that is, two system components. At this time, the raw materials of the two system components are BaCO3, CaCO3, TiO2 and ZrO2. The two system compositions respectively meet 65mol%Ba(Zr 0.2 Ti 0.8 )O3-35mol%(Ba 0.7 Ca 0.3 )TiO3 (BCZT-35 for short) and 50mol%Ba(Zr 0.2 Ti 0.8)O3-50mol%(Ba 0.7 Ca 0.3 )TiO3 (BCZT-50 for short). The above two systems are respectively subjected to the following operations according to steps 101 to 103:
[0144] (1) Add anhydrous ethanol to BaCO3, CaCO3, TiO2 and ZrO2 in a ball mill (the mass ratio of the mixed powder to anhydrous ethanol is 1:1.4), place the ball mill in a planetary ball mill, and mill at 300 r / min for 4 h to obtain a first slurry;
[0145] (2) drying the first slurry at 80° C. for 12 h, and sifting the first slurry through 60-mesh and 100-mesh sieves, respectively. The sieved first slurry is sintered at 1350° C. for 4 h to obtain a first powder;
[0146] (3) The first powder was sieved with 60-mesh and 100-mesh sieves in turn, and the sieved powder was placed in a planetary ball mill and maintained at 300 r / min for secondary ball milling for 8 h (at this time, the mass ratio of the first powder to anhydrous ethanol was 1:1.4), and then dried at 80°C for 12 h to obtain a second slurry;
[0147] (4) mixing 8 wt % of polyvinyl alcohol glue into the first slurry to obtain a second powder having a particle size between 60 and 100 meshes;
[0148] (5) The second powders of the two systems are sequentially loaded into the mold. Each time a layer is added, it is pre-pressed with a pressure of 1 MPa. After the two layers are stacked, it is pressed with a pressure of 20 MPa for 3 minutes to obtain a green body; the green body is placed in a sintering furnace, and the temperature is increased from 25°C to 500°C at a heating rate of 100°C / h, and kept at this temperature for 1 hour; then the temperature is further increased from 500°C to 1500°C at a heating rate of 100°C / h, and kept at this temperature for 4 hours, and then the temperature is naturally reduced to obtain a laminated ceramic substrate;
[0149] The upper and lower surfaces of the multilayer ceramic substrate were polished with 600-mesh and 1000-mesh sandpapers respectively, and silver paste was applied on the upper and lower surfaces of the multilayer ceramic substrate. The multilayer ceramic substrate coated with silver paste was heated from room temperature to 800°C at a heating rate of 150°C / h, kept warm for 40 minutes, and then cooled naturally to obtain a two-layer lead-free piezoelectric ceramic.
[0150] Example 2
[0151] In this embodiment, the ceramic is divided into three layers, namely, three system components. At this time, the raw materials of the three system components are BaCO3, CaCO3, TiO2 and ZrO2. The three system compositions respectively meet the requirements of 65mol%Ba(Zr 0.2 Ti 0.8 )O3-35mol%(Ba 0.7Ca 0.3 )TiO3 (BCZT-35 for short), 50mol%Ba(Zr 0.2 Ti 0.8 )O3-50mol%(Ba 0.7 Ca 0.3 )TiO3 (BCZT-50 for short) and 40mol%Ba(Zr 0.2 Ti 0.8 )O3-60mol%(Ba 0.7 Ca 0.3 )TiO3 (BCZT-60 for short). The above three systems are respectively subjected to the following operations according to steps 101 to 103:
[0152] (1) Add anhydrous ethanol to BaCO3, CaCO3, TiO2 and ZrO2 in a ball mill (the mass ratio of the mixed powder to anhydrous ethanol is 1:1.4), place the ball mill in a planetary ball mill, and mill at 300 r / min for 4 h to obtain a first slurry;
[0153] (2) drying the first slurry at 80° C. for 12 h, and sifting the first slurry through 60-mesh and 100-mesh sieves, respectively. The sieved first slurry is sintered at 1350° C. for 4 h to obtain a first powder;
[0154] (3) The first powder was sieved with 60-mesh and 100-mesh sieves in turn, and the sieved powder was placed in a planetary ball mill and maintained at 300 r / min for secondary ball milling for 8 h (at this time, the mass ratio of the first powder to anhydrous ethanol was 1:1.4), and then dried at 80°C for 12 h to obtain a second slurry;
[0155] (4) mixing 8 wt % of polyvinyl alcohol glue into the first slurry to obtain a second powder having a particle size between 60 and 100 meshes;
[0156] (5) The second powders of the three systems are loaded into the mold in a step-by-step manner. Each time a layer is added, it is pre-pressed with a pressure of 1 MPa. After the three layers are stacked, it is pressed with a pressure of 20 MPa for 3 minutes to obtain a green body; the green body is placed in a sintering furnace, and the temperature is increased from 25°C to 500°C at a heating rate of 100°C / h, and kept at this temperature for 1 hour; then the temperature is further increased from 500°C to 1500°C at a heating rate of 100°C / h, and kept at this temperature for 4 hours, and then the temperature is naturally reduced to obtain a laminated ceramic substrate;
[0157] The upper and lower surfaces of the multilayer ceramic substrate were polished with 600-mesh and 1000-mesh sandpapers respectively, and silver paste was applied on the upper and lower surfaces of the multilayer ceramic substrate. The multilayer ceramic substrate coated with silver paste was heated from room temperature to 800°C at a heating rate of 150°C / h, kept warm for 40 minutes, and then cooled naturally to obtain a three-layer lead-free piezoelectric ceramic.
[0158] Example 3
[0159] In this embodiment, the ceramic is divided into 5 layers, that is, 5 system components. At this time, the raw materials of the 5 system components are BaCO3, CaCO3, TiO2 and ZrO2. The 3 system compositions respectively meet 65mol%Ba(Zr 0.2 Ti 0.8 )O3-35mol%(Ba 0.7 Ca 0.3 )TiO3 (BCZT-35 for short), 60mol%Ba(Zr 0.2 Ti 0.8 )O3-40mol%(Ba 0.7 Ca 0.3 )TiO3 (BCZT-40 for short),
[0160] 55mol%Ba(Zr 0.2 Ti 0.8 )O3-45mol%(Ba 0.7 Ca 0.3 )TiO3 (BCZT-45 for short),
[0161] 50mol%Ba(Zr 0.2 Ti 0.8 )O3-50mol%(Ba 0.7 Ca 0.3 )TiO3 (BCZT-50 for short),
[0162] 45mol%Ba(Zr 0.2 Ti 0.8 )O3-55mol%(Ba 0.7 Ca 0.3 )TiO3 (BCZT-55 for short). The above five system compositions are respectively operated as follows according to steps 101 to 103:
[0163] (1) Add anhydrous ethanol to BaCO3, CaCO3, TiO2 and ZrO2 in a ball mill (the mass ratio of the mixed powder to anhydrous ethanol is 1:1.4), place the ball mill in a planetary ball mill, and mill at 300 r / min for 4 h to obtain a first slurry;
[0164] (2) drying the first slurry at 80° C. for 12 h, and sifting the first slurry through 60-mesh and 100-mesh sieves, respectively. The sieved first slurry is sintered at 1350° C. for 4 h to obtain a first powder;
[0165] (3) The first powder was sieved with 60-mesh and 100-mesh sieves in turn, and the sieved powder was placed in a planetary ball mill and maintained at 300 r / min for secondary ball milling for 8 h (at this time, the mass ratio of the first powder to anhydrous ethanol was 1:1.4), and then dried at 80°C for 12 h to obtain a second slurry;
[0166] (4) mixing 8 wt % of polyvinyl alcohol glue into the first slurry to obtain a second powder having a particle size between 60 and 100 meshes;
[0167] (5) The second powders of the five systems are loaded into the mold in a step-by-step manner. Each time a layer is added, it is pre-pressed with a pressure of 1 MPa. After the three layers are stacked, it is pressed with a pressure of 20 MPa for 3 minutes to obtain a green body; the green body is placed in a sintering furnace, and the temperature is increased from 25°C to 500°C at a heating rate of 100°C / h, and kept at this temperature for 1 hour; then the temperature is further increased from 500°C to 1500°C at a heating rate of 100°C / h, and kept at this temperature for 4 hours, and then the temperature is naturally reduced to obtain a laminated ceramic substrate;
[0168] The upper and lower surfaces of the multilayer ceramic substrate were polished with 600-mesh and 1000-mesh sandpapers respectively, and silver paste was applied on the upper and lower surfaces of the multilayer ceramic substrate. The multilayer ceramic substrate coated with silver paste was heated from room temperature to 800°C at a heating rate of 150°C / h, kept warm for 40 minutes, and then cooled naturally to obtain a 5-layer lead-free piezoelectric ceramic.
[0169] Figure 1 The comparison diagram of the dielectric temperature spectrum of the ceramics obtained in Examples 1-3 is shown. It can be seen that no obvious dielectric peak is observed in the temperature range of 25°C-80°C, indicating that the dielectric response of the lead-free laminated piezoelectric ceramic has good temperature stability. It can be understood that the lead-free laminated piezoelectric ceramic and its preparation method disclosed in the present invention both embody the key to the inventive concept of the present invention. In theory, the general formula and ratio can be further adjusted so that the dielectric response of the lead-free laminated piezoelectric ceramic still shows good temperature stability in different specific temperature ranges.
[0170] It should be noted that Figure 1 ε in the vertical coordinate r Represents the dielectric constant
[0171] Figure 2 The d of the ceramics prepared in Examples 1-3 varies with temperature. 33From the comparison chart, it can be seen that at 25°C, the piezoelectric coefficients of the three ceramics decrease in turn, namely 350pC / N, 300pC / N and 200pC / N, respectively. The piezoelectric coefficients of the three ceramics remain stable within 20-60°C. At this time, with the superposition of components, they show a "hard" characteristic, that is, the coercive field gradually increases, resulting in a decrease in their piezoelectric coefficients. However, this also balances the increase in the activity of the dipole domain and the decrease in the long-range order of the ferroelectric domain due to temperature, thereby obtaining good temperature stability. Within 20-60°C, the piezoelectric performance of the ceramics prepared in Example 1 is the best. It can be seen from this that Figure 1 , Figure 2 It is further confirmed that: preferably, the working temperature of the multilayer lead-free piezoelectric ceramic is 25-80°C, and more preferably, the working temperature of the multilayer lead-free piezoelectric ceramic is 25-60°C.
[0172] It should be noted that d 33 is the piezoelectric coefficient.
[0173] Figure 3 The relationship between the polarization strength and the electric field of the ceramics obtained in Examples 1-3 is shown in a curve diagram. The coercive fields of the three ceramics obtained in Examples 1-3 are 1.83 kV / cm, 2.53 kV / cm and 2.78 kV / cm, respectively. That is, as the coercive field gradually increases, the domain is not easy to flip under the action of the electric field, and the piezoelectric coefficient decreases. It can be seen that the ceramic polarization performance obtained in Example 1 is the best.
[0174] Figure 4 The dielectric temperature spectrum results of single-layer systems (i.e. BCZT-35, BCZT-40, BCZT-45, BCZT-50, BCZT-55 and BCZT-60) are shown. It can be seen that each system has a relatively obvious dielectric peak. The main reason is the polarization enhancement caused by the phase change. Therefore, there is a strong piezoelectric response and dielectric response at the phase change, and a higher piezoelectric coefficient can also be obtained. However, it will also lead to the instability of the piezoelectric coefficient with temperature.
[0175] The following table further shows the dielectric constant and dielectric peak value of the above-mentioned single-layer systems and the ceramics prepared in Examples 1-3 at room temperature:
[0176]
[0177] It can be seen that the dielectric constant and dielectric peak of the ceramics prepared in Examples 1-3 do not show obvious differences relative to each single-layer system, indicating that the laminated composite ceramic structure has good uniformity and stability in dielectric properties, can effectively maintain the dielectric properties of single-layer materials, and the interlayer interaction has little effect on the overall dielectric properties.
[0178] Figure 5The graph shows the variation of the piezoelectric coefficient with temperature of the traditional single-layer systems (i.e. BCZT-35, BCZT-40, BCZT-45, BCZT-50, BCZT-55 and BCZT-60). It can be seen from the graph that the highest piezoelectric coefficient of each system is only obtained at one temperature point, indicating that its temperature stability is poor.
[0179] It is obvious from the above that the laminated lead-free piezoelectric ceramic disclosed in the present invention exhibits excellent dielectric response characteristics and piezoelectric properties due to its laminated structure and good temperature stability.
[0180] The present invention provides a piezoelectric sensor, comprising a layer of silver electrodes coated on both end surfaces of the above-mentioned laminated lead-free piezoelectric ceramic and fired in an integrated manner to obtain a piezoelectric sensor element, an elastic diaphragm, a signal processing circuit and a housing;
[0181] An elastic diaphragm is arranged in the housing;
[0182] A piezoelectric sensing element is adhered to the elastic diaphragm;
[0183] The piezoelectric sensor element is connected to a signal processing circuit, and the signal processing circuit is used to perform charge conversion, amplification processing and filtering processing on the output signal.
[0184] It should be noted that the piezoelectric sensor provided by the present invention, by coating a layer of silver electrode on the two end surfaces of the laminated lead-free piezoelectric ceramic provided by the present invention, does not need built-in electrodes, saves the design and preparation steps of built-in electrodes, and does not need to consider the positioning, connection and compatibility of built-in electrodes with piezoelectric ceramic materials. It greatly simplifies the preparation process, reduces the process links, reduces the probability of errors in the production process, improves production efficiency, and is suitable for large-scale production of laminated lead-free piezoelectric ceramics and piezoelectric sensors; and because the present invention adopts a lead-free system, it also has green and environmentally friendly characteristics.
[0185] Furthermore, a layer of silver electrode is coated on the two end surfaces of the piezoelectric ceramic. Through the coating process, for example, the thickness of the silver electrode can be more accurately controlled. For piezoelectric sensor elements for high-frequency applications, a thinner electrode thickness (such as 5-10 microns) is required to reduce the impact on piezoelectric performance; while for low-frequency or high-power applications, thicker electrodes (such as 20-50 microns) are required to improve conductivity and mechanical strength.
[0186] Furthermore, the coating process can form a chemical bond between the silver electrode and the surface of the piezoelectric ceramic, thereby significantly improving the adhesion of the electrode. Compared with the existing coating process, the combination of the coated silver electrode and the surface of the piezoelectric ceramic usually relies mainly on physical adsorption or simple mechanical adhesion, and the adhesion is relatively weak. In actual use, it is easy to fall off or be damaged by external factors. When the temperature changes, for example, in the common operating temperature range of 25-60℃, the performance of the piezoelectric ceramic may fluctuate greatly due to temperature changes, reducing its reliability and practicality; and the coating process combined with the laminated structure can further improve the performance of the piezoelectric ceramic. The laminated structure makes the ceramic phase boundary distributed in a wide temperature range, effectively reducing the fluctuation of piezoelectric performance caused by temperature changes, and improving the reliability of the ceramic in an environment of 25-60℃. The stable electrode attachment brought by the coating process provides a guarantee for the performance of the laminated structure, so that the entire piezoelectric ceramic system can maintain good performance at different temperatures. In addition, by adjusting the components of each layer, the ceramic can also exhibit excellent dielectric response characteristics within a specific temperature range, while improving the temperature stability of the piezoelectric performance of the ceramic. The synergistic effect of the coating process, the stacked structure and the component adjustment enables piezoelectric ceramics to maintain high performance and high reliability in complex temperature environments, meeting the needs of various practical applications.
[0187] The elastic diaphragm is a thin film component that can produce elastic deformation when subjected to force. The material of the elastic diaphragm is preferably polyimide, which has excellent high temperature resistance, chemical stability and mechanical properties. The elastic modulus of the polyimide elastic diaphragm is low, it can produce large elastic deformation, and is sensitive to changes in external force. At the same time, polyimide has good insulation properties and will not interfere with the electrical signals of the piezoelectric sensor element.
[0188] The signal processing circuit includes a charge amplifier, an operational amplifier, and a passive filter;
[0189] Piezoelectric sensing elements will generate charge signals when subjected to external forces. The function of the charge amplifier is to convert these weak charge signals into voltage signals. An operational amplifier is an electronic device with high gain, high input impedance and low output impedance, which can amplify the input signal. The passive filter is an LC bandpass filter, which consists of a resistor, a C0G / NP0 capacitor and an air core inductor. The C0G / NP0 capacitor and the air core inductor are connected in parallel and then in series with the resistor. By selecting inductors and capacitors with high temperature stability (such as air core inductors and C0G / NP0 capacitors), the filter can maintain a stable frequency response within 25-60°C.
[0190] See also Figure 7 The present invention provides a method for preparing a piezoelectric sensor, comprising:
[0191] Step 201: coating a layer of silver electrode on both end surfaces of the laminated lead-free piezoelectric ceramic and performing integrated firing to obtain a piezoelectric sensing element, wherein the integrated firing includes silver firing, polarization and packaging.
[0192] Step 202: Paste the piezoelectric sensor element onto the elastic diaphragm.
[0193] Step 203: Connect the electrodes of the piezoelectric sensor element to the signal processing circuit.
[0194] Step 204: Place the assembled piezoelectric sensor element into a housing for sealing and packaging to obtain a piezoelectric sensor.
[0195] In the embodiment of the present invention, a layer of silver electrode is coated on both sides of the laminated lead-free piezoelectric ceramic, and a piezoelectric sensor element is obtained by integrated firing. The integrated firing includes silver firing treatment, polarization treatment and packaging treatment. Specifically, the laminated lead-free piezoelectric ceramic coated with silver electrodes is placed in a high-temperature furnace, and the silver firing temperature is set between 700-900°C, and the holding time is 1- The silver-burning treatment is to form a good bond between the silver electrodes coated on the two end surfaces of the laminated lead-free piezoelectric ceramic and the ceramic substrate, and to improve the adhesion and conductivity of the electrode. The laminated lead-free piezoelectric ceramic after the silver-burning treatment is placed in a polarization electric field with a polarization electric field strength of 3 kV / mm, a polarization temperature of 150°C, and a polarization time of 15 minutes, so as to make the electric domains inside the laminated lead-free piezoelectric ceramic oriented under the action of the electric field, so that the laminated lead-free piezoelectric ceramic has a piezoelectric effect. Ceramic packaging is used to seal the piezoelectric ceramic in a ceramic shell by welding, and then the internal gaps are filled with potting glue to protect and fix the piezoelectric ceramic and the silver electrodes from the influence of the external environment.
[0196] Glue the piezoelectric sensor element onto the elastic diaphragm to ensure that it is firmly glued and can effectively transmit force.
[0197] The electrodes of the piezoelectric sensor element are connected to the signal processing circuit, the electrodes of the piezoelectric sensor element are connected to the input end of the charge amplifier, the output end of the charge amplifier is connected to the input end of the operational amplifier, and the output end of the operational amplifier is connected to the input end of the passive filter, so as to perform charge conversion, amplification processing and filtering processing on the output signal.
[0198] The assembled sensor element is placed in a housing and sealed to obtain a piezoelectric sensor with high piezoelectric performance.
[0199] It is worth mentioning that the method for preparing the laminated lead-free piezoelectric ceramics provided by the present invention is simple and efficient, and can be prepared by only one calcination. Moreover, the laminated lead-free piezoelectric ceramics used to prepare piezoelectric sensors only need to be coated with silver electrodes once on the upper and lower surfaces, and there are no built-in electrodes. This fully demonstrates that the method disclosed by the present invention, whether it is used to obtain laminated lead-free piezoelectric ceramics or further prepare piezoelectric sensors, has the characteristics of simple and efficient process. There is no doubt that this preparation method is particularly suitable for large-scale production of laminated lead-free piezoelectric ceramics and piezoelectric sensors thereof; and since the present invention adopts a lead-free system, it also has the characteristics of being green and environmentally friendly.
[0200] Those skilled in the art can clearly understand that, for the convenience and brevity of description, the specific working processes of the systems, devices and units described above can refer to the corresponding processes in the aforementioned method embodiments and will not be repeated here.
[0201] In the several embodiments provided in the present application, it should be understood that the disclosed systems, devices and methods can be implemented in other ways. For example, the device embodiments described above are only schematic. For example, the division of the units is only a logical function division. There may be other division methods in actual implementation, such as multiple units or components can be combined or integrated into another system, or some features can be ignored or not executed. Another point is that the mutual coupling or direct coupling or communication connection shown or discussed can be an indirect coupling or communication connection through some interfaces, devices or units, which can be electrical, mechanical or other forms.
[0202] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A multilayer lead-free piezoelectric ceramic, characterized in that: including multiple layers of lead-free piezoelectric ceramic layers; The lead-free piezoelectric ceramic layers are laminated layer by layer to form a laminated lead-free piezoelectric ceramic; The composition of each lead-free piezoelectric ceramic layer satisfies: (100-x) mol% Ba(Zr 0.2 Ti 0.8 )O3–xmol%(Ba 0.7 Ca 0.3 )TiO3, wherein x is a numerical value of molar percentage, 35≤x≤65.
2. The lead-free multilayer piezoelectric ceramic according to claim 1, characterized in that: The number of the lead-free piezoelectric ceramic layers is 2 to 5.
3. The lead-free multilayer piezoelectric ceramic according to claim 1, characterized in that: The molar percentage values of the components of the multiple layers of the lead-free piezoelectric ceramic layers are distributed in a step-like manner and are different from each other.
4. The lead-free multilayer piezoelectric ceramic according to claim 1, characterized in that: The components of the lead-free piezoelectric ceramic layers of the adjacent two layers are Ba(Zr 0.2 Ti 0.8 )O3 mole percentage and (Ba 0.7 Ca 0.3 )The numerical difference of the molar percentage of TiO3 is between 5 and 15 mol%.
5. The lead-free multilayer piezoelectric ceramic according to claim 1, characterized in that: The piezoelectric coefficient of the stacked lead-free piezoelectric ceramic is 200-350 pc / N.
6. The lead-free multilayer piezoelectric ceramic according to claim 1, characterized in that: The ceramic coercive field of the stacked lead-free piezoelectric ceramic is 1.8-2.8 kV / cm.
7. A method for preparing the lead-free laminated piezoelectric ceramic according to any one of claims 1 to 6, characterized in that: include: Barium source, calcium source, zirconium source and titanium source are used as raw materials. The raw materials are divided into the following components: (100-x)mol%Ba(Zr 0.2 Ti 0.8 )O3–xmol%(Ba 0.7 Ca 0.3 )TiO3 is prepared, wherein x is a value of molar percentage, 35≤x≤65; Based on the above raw materials configured for each layer, powder preparation processing is performed respectively to obtain the second powder of each layer; The second powder of each layer is post-processed to obtain a laminated lead-free piezoelectric ceramic.
8. The preparation method according to claim 7, characterized in that: The above raw materials configured on each layer are respectively subjected to powder preparation processing to obtain the second powder of each layer, including: The above-mentioned raw materials prepared for each layer are mixed and subjected to a ball milling process to obtain the first slurry of each layer; Sintering the first slurry of each layer to obtain the first powder of each layer; The first powder of each layer is ball-milled for a second time to obtain the second slurry of each layer; The second slurry of each layer is granulated to obtain the second powder of each layer.
9. A piezoelectric sensor, characterized in that: The method comprises coating a layer of silver electrodes on both end surfaces of the laminated lead-free piezoelectric ceramic according to any one of claims 1 to 6 and firing the resulting piezoelectric sensing element, elastic diaphragm, signal processing circuit and housing; The elastic diaphragm is arranged in the housing; The piezoelectric sensing element is adhered to the elastic diaphragm; The piezoelectric sensor element is connected to the signal processing circuit, and the signal processing circuit is used to perform charge conversion, amplification processing and filtering processing on the output signal.
10. A method for preparing the piezoelectric sensor according to claim 9, characterized in that: include: A layer of silver electrode is coated on the two end surfaces of the stacked lead-free piezoelectric ceramic and the piezoelectric sensing element is obtained by integrated firing, wherein the integrated firing includes silver firing, polarization and packaging. Paste the piezoelectric sensor element onto the elastic diaphragm; connecting the electrodes of the piezoelectric sensing element to a signal processing circuit; The assembled piezoelectric sensor element is placed in a housing for sealing and packaging to obtain a piezoelectric sensor.
Citation Information
Patent Citations
Lead-free calcium barium zirconate titanate piezoelectric ceramics and preparation method thereof
CN101935212A
Gradient-doped sodium-bismuth-titanate-based multilayer leadless piezoelectric ceramic
CN107903055A
Preparation method of gradient ceramic piezoelectric material, piezoelectric material and piezoelectric sensor
CN111747738A
Potassium-sodium niobate-based lead-free piezoelectric ceramic with gradient components and preparation method thereof
CN113666744A
Ceramic material with thermal stability piezoelectric coefficient and preparation method thereof
CN117125981A